Pengembangan Model Desain Instruksionalnai Berbasis Humanistik untuk Penguatan Karakter Religius Peserta Didik - Elcha Athifa; Dinizen; Gusmaneli (Indo Publishing, 2025)
This study aims to examine and develop a humanistic-based instructional design model for Islamic Religious Education (IRE) as a strategy to strengthen students' religious character in the modern era. The background of this research stems from the reality that the PAI learning process in various educational institutions still tends to be oriented towards the transfer of knowledge alone, while affective and spiritual aspects are often neglected. In this context, the humanistic approach is relevant because it places students as the main subjects of learning who have spiritual, emotional, and intellectual potential that needs to be developed in a balanced manner. This study uses the library research method by examining various literature sources such as books, scientific journals, and academic articles that discuss instructional design theory, humanistic principles, and Islamic religious education. The collected data were analyzed using content analysis techniques to find conceptual links between learning design theory and humanistic values in the context of PAI. The results of the study show that humanistic-based learning design is capable of creating a dialogical, reflective, and empathetic learning atmosphere, so that students not only understand Islamic teachings cognitively, but also internalize them in their daily behavior and attitudes, such as sincerity, responsibility, and social awareness. Thus, the application of a humanistic-based PAI instructional design model can be an innovative alternative in building a strong religious character that is relevant to the challenges of 21st-century education. This study concludes that the application of a humanistic-based instructional design model can be a strategic and innovative alternative in strengthening the religious character of students, while also responding to the challenges of Islamic education amid current social changes and technological advances.